-2/7y=-1/7

Simple and best practice solution for -2/7y=-1/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/7y=-1/7 equation:


y in (-oo:+oo)

(-2/7)*y = -1/7 // + -1/7

(-2/7)*y-(-1/7) = 0

(-2/7)*y+1/7 = 0

1/7-2/7*y = 0 // - 1/7

-2/7*y = -1/7 // : -2/7

y = -1/7/(-2/7)

y = 1/2

y = 1/2

See similar equations:

| x+4x+6=46 | | 63x+63=x^3+3x^2-61x | | 1/3x3.14x36x12 | | -7/2z=-7 | | 4.1b-3.22=4.3b | | 7.8x=499.2 | | 14.5d+9.98=3d-18.77 | | 54+36=k | | h/9=11 | | 3x^2+6+2=0 | | f(x)=18x^2+2610x-113400 | | X^3+3x^2-61=63 | | 1/3x=-73/9 | | -14.25-7.9q-14.43=0.6q+10.42 | | 1/3x=-73/8 | | K=-55+6k | | -13p-14-18=20-17p | | A+2.25=2a-1 | | 20-2Q=2Q+8 | | -17t+5=-4-8t | | (2x^2-25x)=(3x^2+60) | | 2x-6y=48 | | -3/7k=9/5 | | -12+11y=10y | | 20-y=16 | | 1/3x=243 | | 1/3•(2y)^0•x^-3 | | x/2-5=-1 | | 2h+9=-9-7h | | 243=1/3bh | | -6+g-4g=-9-2g | | 0+2y=-1 |

Equations solver categories